Pelatihan Pembuatan Pupuk Organik Cair pada Lembaga Masyarakat Desa Hutan (LMDH) Desa Pringsurat Kecamatan Kajen Kabupaten Pekalongan: Training on the Production of Liquid Organic Fertilizer for the Forest Village Community Institution (LMDH) in Pringsurat Village, Kajen Subdistrict, Pekalongan Regency - Supriyanto, Eka Adi; Afiatan, Arbina Satria; Badrudin, Ubad; Sajuri, Sajuri; Al Ramadhani, Farchan Mushaf; Silfiyani, Silfiyani; Arwanda, Muhammad; Sari, Diana Kartika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Organic farming has become increasingly essential to ensure environmental sustainability and public health. One approach to supporting this practice is using liquid organic fertilizers, which not only enhance soil fertility naturally but also aid in managing organic waste. However, limited knowledge and access to agricultural technology often pose challenges for the Pringsurat Village, Pekalongan Regency community, where most of the population works in the farming and plantation sectors. To address these challenges, a training program on liquid organic fertilizer production was conducted, involving 20 members of LMDH in Pringsurat Village—this community service aimed to enhance participants' knowledge and skills. The methods employed included the dissemination of information and hands-on training in the production of liquid organic fertilizer. The results showed a significant increase in participants' knowledge regarding liquid organic fertilizers in terms of benefits and production techniques. Before the training, most participants lacked sufficient understanding of liquid organic fertilizers; however, over 70% of participants demonstrated improved comprehension after the training. Participants' interest in developing liquid organic fertilizers increased significantly, from 55% before the training to 90% afterward. Despite these positive outcomes, challenges remain in applying this knowledge, particularly related to educational factors and individual perceptions. Therefore, a more intensive and sustained approach is required to ensure the successful adoption of sustainable agricultural technologies within the community.